2022
DOI: 10.21037/apm-22-1306
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CDK4/6 inhibitors combined with endocrine therapy versus endocrine therapy alone in hormone receptor-positive, HER2-negative, advanced breast cancer: a systematic review and meta-analysis

Abstract: Background: In previous studies on the application of cyclin-dependent kinase 4/6 (CDK4/6) inhibitors combined with endocrine therapy in advanced breast cancer, the outcomes of overall survival (OS) were inconsistent. This systematic review and meta-analysis aimed to further evaluate the clinical efficacy and safety of CDK4/6 inhibitors combined with endocrine therapy on patients with hormone receptor (HR)positive and human epidermal growth factor receptor 2 (HER2)-negative advanced breast cancer.Methods: Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…For HR+/HER2− ABC, there was broad agreement in the MAs findings that CDK4/6 inhibitors were associated with significant improvements in PFS, OS, ORR, and CBR, affirming the short- and long-term clinical efficacy of combination therapy for ABC. Notably, Munzone et al ( 2021 ) looked at PFS2 and TTC outcomes and found that combination therapy improved PFS2 and TTC, which was consistent with the results of a MA published during the review of this study (Dai et al 2022 ), suggesting that combination therapy may delay the onset of endocrine resistance and delay the duration of chemotherapy and chemotherapy-related toxicity, which may translate into a significant OS benefit and maintain a better quality of life for patients over a longer period of time.…”
Section: Discussionsupporting
confidence: 86%
“…For HR+/HER2− ABC, there was broad agreement in the MAs findings that CDK4/6 inhibitors were associated with significant improvements in PFS, OS, ORR, and CBR, affirming the short- and long-term clinical efficacy of combination therapy for ABC. Notably, Munzone et al ( 2021 ) looked at PFS2 and TTC outcomes and found that combination therapy improved PFS2 and TTC, which was consistent with the results of a MA published during the review of this study (Dai et al 2022 ), suggesting that combination therapy may delay the onset of endocrine resistance and delay the duration of chemotherapy and chemotherapy-related toxicity, which may translate into a significant OS benefit and maintain a better quality of life for patients over a longer period of time.…”
Section: Discussionsupporting
confidence: 86%
“…The development of oral endocrine drugs has significantly improved the therapeutic strategy for breast cancer, providing patients with convenient and effective alternatives to traditional intravenous chemotherapy. 1 However, despite their benefits, adherence to and persistence of oral anticancer treatments remain a major challenge. 2 Adherence refers to the degree to which patients adhere to their prescribed medication regimen, while persistence refers to the length of time patients continue to take their medication as directed.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the confluence of targeted drugs such as Cyclin-Dependent Kinase4/6 (CDK4/6) inhibitors with ET has emerged as a burgeoning area of research. Numerous randomized controlled trials (RCTs) have conclusively demonstrated that the combination of CDK4/6 inhibitors with ET effectively manages HR+/HER2-breast cancer, curtails the dissemination of cancer cells, and markedly improves patients' quality of life and survival rates [ [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%